Parasitism in ecosystem engineer species: A key factor controlling marine ecosystem functioning. Issue 9 (4th May 2020) - Pascal, Ludovic; Grémare, Antoine; de Montaudouin, Xavier; Deflandre, Bruno; Romero‐Ramirez, Alicia; Maire, Olivier
Abstract: Although parasites represent a substantial part of marine communities' biomass and diversity, their influence on ecosystem functioning, especially via the modification of host behaviour, remains largely unknown. Here, we explored the effects of the bopyrid ectoparasite Gyge branchialis on the engineering activities of the thalassinid crustacean Upogebia pusilla and the cascading effects on intertidal ecosystem processes (e.g. sediment bioturbation) and functions (e.g. nutrient regeneration). Laboratory experiments revealed that the overall activity level of parasitized mud shrimp is reduced by a factor 3.3 due to a decrease in time allocated to burrowing and ventilating activities (by factors 1.9 and 2.9, respectively). Decrease in activity level led to strong reductions of bioturbation rates and biogeochemical fluxes at the sediment–water interface. Given the world‐wide distribution of mud shrimp and their key role in biogeochemical processes, parasite‐mediated alteration of their engineering behaviour has undoubtedly broad ecological impacts on marine coastal systems functioning. Our results illustrate further the need to consider host–parasite interactions (including trait‐mediated indirect effects) when assessing the contribution of species to ecosystem properties, functions and services. Abstract : The originality and the novelty of this work lies in the association of behaviour, ecology, biogeochemistry and parasitology in one study. This study characterises the cascading effects of parasite infestation from modification of host behaviour to the alteration of ecosystem functioning via the decrease of host bioturbation intensity.